Modified Alternating Positive Semidefinite Splitting Preconditioner for Time-Harmonic Eddy Current Models (Journal of Computational Mathematics, 2021)
In this paper, we consider a modified alternating positive semidefinite splitting preconditioner for solving the saddle point problems arising from the finite element discretizationof the hybrid formulation of the time-harmonic eddy current model. The eigenvalue distribution and an upper bound of the degree of the minimal polynomial of the preconditionedmatrix are studied for both simple and general topology. Numerical results demonstrate theeffectiveness of the proposed preconditioner when it is used to accelerate the convergencerate of Krylov subspace methods such as GMRES.
Keywords: Time-harmonic eddy current model; Saddle point problem; Eigenvalue distribution; Preconditioner.